D. MOVILLA - 99 Years of the Housing Question in Sweden - Campaña, Esperanza (ZARCH, 2019)
Daniel Movilla Vega (ed.) 99 Years of the housing question in Sweden Based on an ArkDes exhibition curated by Dan Hallemar Lund: Studentlitteratur, 2017. 325 págs. Tapa blanda. Idioma: inglés. ISBN-10: 9144120478. ISBN-13: 978-9144120478